2014
DOI: 10.1590/s0004-28032014000100003
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical Nutritional Profile of Liver Cirrhosis Patients With Hepatocellular Carcinoma

Abstract: -Context -Liver cirrhosis patients with hepatocellular carcinoma present nutritional alterations and metabolic disorders that negatively impact the prognosis. Objective -The objective is to identify alterations in the metabolism of macro and micronutrients among liver cirrhosis patients with and without hepatocellular carcinoma and their relation to the Child-Turcote-Pugh score and Barcelona Clinic Liver Cancer staging. Methods -Analytical transversal study, with 31 hepatocellular carcinoma patients and 48 liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
9
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
(49 reference statements)
3
9
1
2
Order By: Relevance
“…The reduction of plasma folate in HCC patients may have resulted from various factors. For example, the most common factors are under-nutrition and severe catabolic status which cancer patients suffer from, compromising the plasma folate status [ 14 ]. Moreover, a low folate status was reported to lead to liver damage through oxidative stress and pro-fibrogenic effect [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…The reduction of plasma folate in HCC patients may have resulted from various factors. For example, the most common factors are under-nutrition and severe catabolic status which cancer patients suffer from, compromising the plasma folate status [ 14 ]. Moreover, a low folate status was reported to lead to liver damage through oxidative stress and pro-fibrogenic effect [ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown a close association between UA production and non-alcoholic fatty liver disease (Li et al, 2009;Sirota et al, 2013), liver cancer (Port et al, 2014), and other liver diseases. Hepatocytes are the primary sites of UA generation.…”
Section: Introductionmentioning
confidence: 90%
“…Factors such as anorexia and early satiety, triggered by changes in endogenous leptin, mineral deficiencies and reduction in gastric expandability favor a negative energetic balance, with an imbalance between ingestion and energy intake and expenditure, and PCM may develop as a result[ 14 ]. The zinc and magnesium deficiencies that may be often seen in the population of patients with cirrhosis contribute to the development of dysgeusia, which aggravates the intake capacity[ 15 , 16 ].…”
Section: Malnutrition In Cirrhosismentioning
confidence: 99%